The fact of experience: rethinking political knowledge and civic competence - Cramer, KJ; Toff, B (Cambridge University Press, 2017)
In the study of political knowledge, the emphasis on facts is misplaced. Evidence has grown that predispositions and social contexts shape how individuals are exposed to and interpret facts about politics, and the ready availability of information in the contemporary media environment may exacerbate these biases. We reexamine political knowledge from the bottom up. We look at what citizens themselves treat as relevant to the task of understanding public affairs and how they use this information. We draw upon our research in three different projects involving observation of political talk and elite interviews to do so. We observe that people across a range of levels of political engagement process political information through the lens of their personal experience. Failing to acknowledge this aspect of the act of using political information presents an incomplete empirical understanding of political knowledge. We propose an Expanded Model of Civic Competence that presents an alternative interpretation for what it means to be an informed citizen in a democracy. In this model, the competence of listening to and understanding the different lived experiences of others cannot be considered separately from levels of factual knowledge.